Tradisi Ulak Manah dan Komunikasi Transendental: Studi Masyarakat Muslim Pedalaman Ulu Kapuas - Ibrahim, Ibrahim; Muttaqin, Imron (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article discusses the transcendental communication of the Ulu Kapuas Muslim community, which is represented in the oral tradition of Ulak Manah. Through a descriptive qualitative method that focuses on analyzing the story of the Umung Putri Raja and the Shaman Agreement with the crocodile king, this study found that the Ulu Kapuas Muslim community believed that there was a familial relationship between humans and descendants of crocodiles. This tradition is manifested in the tradition of buang-buang, maintaining relationships and descent, as well as reminding of promises owed. Preservation of these traditions forms transcendental communication between human descendants and crocodile offspring in Ulak Manah.